Airbase vulnerability to conventional cruise-missile and ballistic-missile attacks : technology, scenarios, and U.S. Air Force responses - Stillion, John (RAND, 1999)
As part of a two-year effort to develop an expansive construct of air and space power in the early twenty-first century that capitalizes on forthcoming air and space technologies and concepts of operation and is effective against adversaries with diverse economies, cultures, political institutions, and military capabilities, the research team investigated the possibility that future adversaries might be able to mount effective missile attacks on U.S. Air Force (USAF) main operating bases in critical regions. This report does not assess the relative vulnerabilities of various force elements and facilities; instead, it aids the USAF in addressing a potential vulnerability of its in-theater bases: highly accurate attacks against USAF aircraft on parking ramps at such bases made possible by the proliferation of Global Positioning System (GPS) guidance and submunition warhead technologies. If such attacks are feasible, the current USAF operational concept of high-tempo, parallel strikes from in-theater bases could be put in jeopardy. This report concludes that these guidance and munition technologies could, in fact, put USAF bases at serious risk. The report describes the threat technologies and concept of operation in detail, then explores both short-term responses--such as putting machine-gun teams equipped with night-vision goggles in towers around the bases--and long-term responses--such as operating anywhere in the world from a few secure, hardened, fixed bases with guaranteed access--to these threats.